21.2k views
4 votes
Use the functions f (x)= –x^2 + 8x – 11, g(x) = 14 - 2/3x,and h(x) = -x – 7 to find each function value.

1/2g(-6)+f(-2)=

2 Answers

3 votes

Final answer:

To find the value of 1/2g(-6)+f(-2), evaluate g(-6) and f(-2) and substitute the values into the expression.

Step-by-step explanation:

To find the value of 1/2g(-6)+f(-2), we first need to evaluate the functions g(x) and f(x) at the given values.

g(-6) = 14 - 2/3(-6) = 14 + 4 = 18

f(-2) = -(-2)^2 + 8(-2) - 11 = -4 - 16 - 11 = -31

Now, substitute the values of g(-6) and f(-2) into the expression 1/2g(-6)+f(-2):

1/2(18) + (-31) = 9 - 31 = -22

User Rovanion
by
4.9k points
1 vote
-2f-3g it the right answer
User Manuela Hutter
by
5.4k points